The Use Of Web 2.0 Application In Learning: Investigating The Use Of Chatgpt In Improving Students’ Work - Dwirahma Fadhlika Anjani; Fatayatul Hanani Safrul (Barkah Publishing, 2024)
This study examines the perceptions of students regarding the use of ChatGPT to enhance their homework performance and explores strategies for its optimal application. The integration of artificial intelligence (AI) in education, particularly ChatGPT, has provided students with tools to overcome common academic challenges, such as difficulty understanding instructions and managing time effectively. Despite its potential, the ethical and practical implications of its usage remain underexplored. The study addresses two key questions: (1) What are students' perceptions of using ChatGPT for completing their homework? (2) How does the use of ChatGPT affect students' homework performance? A qualitative approach was adopted, utilizing semi-structured interviews with eight students from Ar-Raniry State Islamic University who had experience using ChatGPT for academic purposes. Students perceive ChatGPT as a valuable tool for generating ideas, improving writing quality, and breaking down complex concepts into simpler terms. It enhances efficiency, allowing faster task completion and better comprehension of study materials. However, concerns about the reliability of responses and overreliance on AI, which could undermine critical thinking and creativity, were raised. ChatGPT contributes positively to academic performance when used as a supplementary tool rather than a replacement for independent learning. Students emphasize the importance of ethical usage to maintain academic integrity and ensure meaningful learning. These findings suggest that ChatGPT has the potential to support education when integrated responsibly, offering valuable insights for educators and institutions seeking to optimize AI tools in academic contexts